A Critical Discourse Analysis of the Aboriginal and Torres Strait Islander Cross Curriculum Priority in the Australian Geography Curriculum ... - Stanford, Bartholomew (University of the Sunshine Coast, Queensland, 2016)
The Australian Curriculum includes Aboriginal and Torres Strait Islander histories and cultures as a Cross Curriculum Priority across all key learning areas. The Australian education system is largely based upon Anglo-Saxon values, beliefs and worldviews. This Critical Discourse Analysis examines the positioning of Aboriginal and Torres Strait Islander content in relation to Geography Curriculum content. The purpose of this research was to understand how Indigenous content has been re-contextualised, to determine how Australian school teachers interpret Indigenous content in disciplinary areas. The positioning of Indigenous content was examined through the application of Critical Discourse Analysis tools. A cultural analysis tool was also used to measure the breadth of content and the depth of perspective of Aboriginal and Torres Strait Islander curriculum content. From all levels of analysis, it was found that Aboriginal and Torres Strait Islander histories and cultures are positioned in states of ...